Descriptions - Neale, Stephen, 1958- (MIT Press, 1990)
In 1905, Bertrand Russell argued that certain logical puzzles are solved if definite descriptions are treated as quantified expressions rather than referential expression, as Frege had thought. Since then, philosophers and, more recently, linguists have debated the relevance of this paradigm to the study of the semantics of natural language. In Descriptions, Stephen Neale provides the first sustained defense and extension of Russell's theory, placing it in the center of a theory of singular and nonsingular descriptive phrases and anaphoric pronouns -- Provided by the publisher.
"A Bradford book."
Keywords: Language and languages -- Philosophy.; Description (Philosophy); Anaphora (Linguistics); Description (Philosophie); Anaphore.; Langage et langues -- Philosophie.; descriptions (documents); descriptive note.; description (activity); PHILOSOPHY -- Epistemology.; Language and languages -- Philosophy; Anapher -- Syntax; Deskriptive Linguistik; Kennzeichnung; Sprachphilosophie; Natuurlijke taal.; Semantiek.; Anafora.; Language -- Philosophy